‘Making the building blocks small’ - the participative and capital-enhancing development of digital literacies in older adults - Feeney, Drew; Ryan, Frances V. C.; Brazier, David; Webster, Gemma (Information Research an international electronic journal, 2025)
Introduction. Older adults are disproportionately affected by deficits in digital literacy development and by present learning environments which are either difficult to access or not conducive to their specific needs. Participatory research frameworks offer compelling approaches to these convergent issues, and opportunities to build capital-enhancing networks around such skills development could place socially situated learning at the heart of effective provision here. Method and analysis. Data was collected via structured surveys and in-person workshop sessions from a cohort of self-defined older adults (N=7) active within the Scottish public library network. The data was examined by quantitative methods and thematic analysis using the NVIVO software. Results. Older adults themselves respond positively to working within a participative ethos, which here allows them to identify, assess and understand their own digital literacy needs and to directly challenge the causes of them. A re-evaluation of both the learning environment and of its consequences on fear and confidence around digital literacies is emergent. Conclusions. Older adults place high value on the creation of peer-led-and-supported social spaces in which to develop digital literacy skillsets. Utilising participative approaches can positively impact this development and shape future research agendas, whilst also unlocking the ongoing and sustainable social capital benefits to be gained from engagement in this way.